Mechanisms of low susceptibility to the disinfectant benzalkonium chloride in a multidrug-resistant environmental isolate of Aeromonas hydrophila - Chacón, Luz; Kuropka, Benno; González-Tortuero, Enrique; Schreiber, Frank; Rojas-Jiménez, Keilor; Rodríguez-Rojas, Alexandro (Frontiers in Microbiology, 2023)
Excessive discharge of quaternary ammonium disinfectants such as benzalkonium chloride (BAC) into aquatic systems can trigger several physiological responses in environmental microorganisms. In this study, we isolated a low susceptible strain of Aeromonas hydrophila, namely INISA09, to from a wastewater treatment plant in Costa Rica. We characterized its phenotypic response upon exposure to three different concentrations of BAC and determined the primary mechanisms related to its resistance using genomic and proteomic tools. The genome of the strain is 4.6-Mb with 4,273 genes, and we found a propound genome rearrangement and thousands of missense mutations when compared to the reference strain A. hydrophila ATCC 7966. We identified 15,762 missense mutations mainly associated with transport, antimicrobial resistance, and outer membrane proteins. In addition, quantitative proteomic analysis revealed the significant upregulation of several efflux pumps and the downregulation of porins when the strain was exposed to three BAC concentrations. Other genes related to membrane fatty acid metabolism and redox metabolic reactions also showed an altered expression. Our findings suggest that the response of A. hydrophila INISA09 to BAC primarily occurs at the membrane level, which is BAC's primary target. This study sheds light on the mechanisms of antimicrobial susceptibility in tropical aquatic environments against a widely-used disinfectant, using an environmental strain that could serve as a new study model.